High‐order realisation of MOSFET‐only band‐pass filters for RF applications. Issue 4 (17th May 2018) - Yesil, Abdullah; Minaei, Shahram
Abstract : The authors present two new metal oxide semiconductor field effect transistor (MOSFET)‐only second‐order voltage and transadmittance‐mode band‐pass filters (BPFs) employing only five transistors without using any passive elements such as a resistor, a capacitor, and an inductor. As a result, both proposed circuits possess low‐power consumption and occupy small chip area. The first proposed filter enjoys low output impedance and offset cancellation for voltage‐mode operation while the second proposed filter has low supply voltage. The centre frequency of both proposed filters can be electronically tuned by varying biasing voltage. To demonstrate the performance of the proposed filters, effects of output transconductance of transistors have been investigated and equations of input referred noise have been obtained. Furthermore, fourth‐order voltage and transadmittance‐mode BPF which is derived the first proposed filter is presented and its simulation results are given. All proposed filters are laid‐out in the Cadence environment using Taiwan semiconductor manufacturing company (TSMC) 0.18 µm complementary metal oxide semiconductor (CMOS) technology parameters. The required chip area of the fourth‐order voltage and transadmittance‐mode band‐pass filter is 1100 μm 2 and the power consumption is about 436 µW.